(untitled) (Research, Society and Development, 2021)
This study aims to describe the clinical and epidemiological characteristics, risk factors and outcome of COVID-19 in pregnant women. This is a quantitative study with a descriptive approach. The sample consisted of 54 volunteers assisted in a high-risk maternity hospital located in Aracaju, Sergipe, Brazil. Data were extracted from medical records and analyzed as maternal sociodemographic variables related to prenatal care, participation and immediate puerperium, the presence or absence of symptoms of COVID-19, admission to the ICU and outcome. Data were generated using absolute and related frequencies. It was also calculated to mean, standard deviation, minimum value, and maximum value of the quantitative variables in IBM® SPSS. Pregnant women aged between 20 and 34 years (64.8%; n=35) and brown (61.1%; n=33) predominated. Regarding the mode of delivery, cesarean sections stood out (76.9%; n= 30). Symptoms such as headache (51.8%; n=28), fever (51.8%; n=28), cough (44.4%; n=24), runny nose (35.1%; n= 19) and dyspnea (20.3%; n=11). Most participants had at least some sign of severity (87%; n=47) and had comorbidities (77.7%; n=42). Three maternal deaths were registered. It is concluded that the presence of comorbidity was a relevant risk factor in participants who developed more severe disease, possibly indicating a predefined profile that contributes to a higher risk of severe maternal outcomes.